Aider moi

exo 1
developper l'expression suivante : A(x)= -1/2( 2x -3)² +2(-1/2x+1)²

exo 2
factoriser chacune les expressions suivantes , puis resoudre f(x)=0
a) f(x)=(x+2)(2x-3) - (2x-3) (1-4x)
b) f(x)=(2x-3)²-(3x-2)²

1

Réponses

2014-05-14T11:24:57+02:00
Exo1
A(x)=-1/2(2x-3)²+2(-1/2x+1)²
A(x)=-1/2(4x²-12x+9)+2(x²/4-x+1)
A(x)=-2x²+6x-9/2+x²/2-2x+2
A(x)=-3x²/2+4x-5/2

Exo2:
a) f(x)=(x+2)(2x-3)-(2x-3)(1-4x)
f(x)=(2x-3)((x+2)-(1-4x))
f(x)=(2x-3)(x+2-1+4x)
f(x)=(2x-3)(5x+1)

f(x)=0
⇔2x-3=0 ou 5x+1=0
⇔x=3/2 ou x=-1/5

b) f(x)=(2x-3)²-(3x-2)²
f(x)=(2x-3+3x-2)(2x-3-3x+2)
f(x)=(5x-5)(-x-1)
f(x)=-5(x-1)(x+1)

f(x)=0
⇔x-1=0 ou x+1=0
⇔x=1 ou x=-1